2003
DOI: 10.1128/cdli.10.6.1078-1084.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mimotopes of the Vi Antigen ofSalmonella entericaSerovar Typhi Identified from Phage Display Peptide Library

Abstract: The capsular polysaccharide Vi antigen (ViCPS) is an essential virulence factor and also a protective antigen of Salmonella enterica serovar Typhi. A random 12-mer phage-displayed peptide library was used to identify mimotopes (epitope analogues) of this antigen by panning against a ViCPS-specific monoclonal antibody (MAb) ATVi. Approximately 75% of the phage clones selected in the fourth round carried the peptide sequence TSHHDSHGLHRV, and the rest of the clones harbored ENHSPVNIAHKL and other related sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…There are many examples demonstrating the potential of phage-born peptides as potential diagnostic reagents. These include a 9-mer peptide fused to the gpVIII protein for the detection of cucumber mosaic virus (Gough et al, 1999), a cyclic heptapeptide on the gpIII protein for the pathotyping of Newcastle disease virus (Ramanujam et al, 2004) and a 12-mer gpIII protein for the identification of the anti-Vi antigen of Salmonella enerica Serovar Typhi (Tang et al, 2003). These together with the results in this study demonstrate that phage displayed peptides show promise as reagents for detection of biological samples.…”
Section: Discussionsupporting
confidence: 62%
“…There are many examples demonstrating the potential of phage-born peptides as potential diagnostic reagents. These include a 9-mer peptide fused to the gpVIII protein for the detection of cucumber mosaic virus (Gough et al, 1999), a cyclic heptapeptide on the gpIII protein for the pathotyping of Newcastle disease virus (Ramanujam et al, 2004) and a 12-mer gpIII protein for the identification of the anti-Vi antigen of Salmonella enerica Serovar Typhi (Tang et al, 2003). These together with the results in this study demonstrate that phage displayed peptides show promise as reagents for detection of biological samples.…”
Section: Discussionsupporting
confidence: 62%
“…The classical typhoid+paratyphoid A+paratyphoid B (TAB) vaccine and oral Salmonella enterica subsp. Typhi (S. Typhi) Ty21a vaccine offer good immunity production in humans, but neither is a complete and ideal vaccine, resulting in the necessity for further studies (Mastroeni & Ménager, 2003;Tang et al, 2003). It has been shown that the S. Typhi Vi capsular polysaccharide (Vi-CPS) subunit vaccine can prevent typhoid fever.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the S. Typhi Vi capsular polysaccharide (Vi-CPS) subunit vaccine can prevent typhoid fever. A single intramuscular injection of this vaccine conferred about 65 and 72 % protection in South Africa and Nepal, respectively (Acharya et al, 1987;Klugman et al, 1987;Szu et al, 1994;Tang et al, 2003;Chibber & Bhardwaj, 2004). The Vi-CPS vaccine has now been licensed in .93 countries worldwide, although it is not commonly used as part of vaccination programmes in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, bacteriophage M13 has been used widely in phage display technology and many peptides and proteins have been displayed successfully on the surface of the particle [6]. The displayed peptides and proteins have been applied in various fields of study including protein-protein interactions [7][8][9], identification of mimotopes for the development of vaccines [10,11], investigation of immune response [12,13], evaluation of small molecules drug candidates [14,15], identifying of peptide ligands for a variety of receptor ligands [16], and development of diagnostic reagents [6,[17][18][19][20]. Recently, M13 has been studied for its uses in nanostructures and nanotechnology for developing nanowires, nanosized energy storage unit and biocomposite fibers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%